Efektivitas Penerapan Model Pembelajaran Problem-Based Learning dalam Pendidikan Agama Islam Siswa SMAN 10 Batanghari - Fitrisia, Rosi; Nurmadiah, Nurmadiah (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study evaluates the effectiveness of implementing the Problem-Based Learning (PBL) method in Islamic Religious Education (PAI) teaching for 10th-grade students at SMAN 10 Batanghari. The primary goal of this research is to enhance students' understanding, engagement, and collaboration skills through a more interactive and contextual approach. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using thematic analysis techniques. The results indicate that the application of the PBL method positively impacts students' understanding of PAI material, particularly on the topic